Determinants of Interest Purchasing Shallot Seeds of Varieties Thai Nganjuk (Tajuk) - Yuliansyah, Dandy; Prasaja*, Mukti; Junaedi, Imam; Pratiwi, Nuris (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The objective of this research is to analyze the factors influencing consumer interest in purchasing Tajuk variety onion seeds. The factors affecting consumer purchase interest include content marketing through YouTube, risk perception, and consumer trust. The research method employed is quantitative, with a purposive sampling technique used to select 85 respondents. Subsequently, the analysis results indicate that content marketing through YouTube does not significantly influence consumer purchase interest in Tajuk variety onion seeds. Risk perception does not have a significant effect on consumer purchase interest in Tajuk variety onion seeds. However, consumer trust has a significant influence on the purchase interest of Tajuk variety onion seeds. Furthermore, it is expected that content marketing through YouTube will provide development in the marketing of agricultural products, especially red onions, and through digital marketing media. Keyword: Content Marketing; Risk Perception; Consumer Confidence; Buying Interest; Shallot Seeds